Fused (Stk36) is a ciliary protein required for central pair assembly and motile cilia orientation in the mammalian oviduct. Issue 11 (10th September 2013) - Nozawa, Yoko Inès; Yao, Erica; Lin, Chuwen; Yang, Jehn‐Hsiahn; Wilson, Christopher W.; Gacayan, Rhodora; Chuang, Pao‐Tien
<x xml:space="preserve">Abstract</x> Background: Motile cilia on the inner lining of the oviductal epithelium play a central role in ovum transport toward the uterus and subsequent fertilization by sperm. While the basic ultrastructure of 9+2 motile cilia (nine peripheral microtubule doublets surrounding a central pair) has been characterized, many important steps of ciliogenesis remain poorly understood. Results: Our previous studies on mammalian Fused (Fu) (Stk36), a putative serine‐threonine kinase, reveal a critical function of Fu in central pair construction and cilia orientation of motile cilia that line the tracheal and ependymal epithelia. These findings identify a novel regulatory component for these processes. In this study, we show that Fu is expressed in the multi‐ciliated oviductal epithelium in several vertebrates, suggesting a conserved function of Fu in the oviduct. In support of this, analysis of Fu‐deficient mouse oviducts uncovers a similar role of Fu in central pair construction and cilia orientation. We also demonstrate that Fu localizes to motile cilia and physically associates with kinesin Kif27 located at the cilium base and known central pair components Spag16 and Pcdp1. Conclusions: Our results delineate a novel pathway for central pair apparatus assembly and add important insight to the biogenesis and function of oviductal motile cilia. Developmental Dynamics 242:1307–1319, 2013. © 2013 Wiley Periodicals, Inc.